TEACHING BY USING VIDEO: WAYS TO MAKE IT MORE MEANINGFUL IN EFL CLASSROOMS - Sitti Hadijah (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
The widespread of English learning videos nowadays reveal that technology has been integrated in English language realm. There are numerous videos that can be deployed as English learning media or sources. As commonly known, the use of video in English Foreign Language (EFL) classrooms can facilitate the students to get more interested in learning and also enhance their communicative competences because they can get rich learning experiences. However, in this advanced technology era, the teachers have to face some challenges in utilizing the video in the classrooms, such as variety of video formats, technology devices, and video techniques. In this case, the teachers have to be able to choose appropriate video, deploy the technology devices, and present it in more interesting and meaningful ways. If the teachers do not know how to figure out the challenges, the video will not work effectively to achieve the teaching and learning objectives. Considering great benefits and challenges of using video in the EFL classrooms, this paper discusses theoretical background to present some meaningful ways of deploying video. It is expected to provide information for English Language teachers to successfully employ the video in their classrooms.